PEMETAAN KONDISI KARANG TEPI (FRINGGING REEF) DAN KUALITAS AIR PANTAI ANGSANA KALIMANTAN SELATAN - Yunandar Yunandar (Environmental Research Center (PPLH) of Udayana University, 2011)
This research aimed to: (a) identified and delineated coverage coral reef area on coastal Angsana based on value spectral; (b) coral reef area’s calculated; (c) coral reef area’s mapping conditions and (d) Estimated of water quality on coastal study area based on field algorithm model. Methods employed in this research was combined field survey, remote sensing and water quality. The result obtained Aster band 321 discovered three of class habitat coral with coverage life coral in middle, sands and rubble mixed on fringing reef and seagrass not found. Life coral discovered on station 1 (6 hectare) and Aster (5 hectare), based on component of population most coral dead dominated on station 1 (3,5 hectare) and (2,5 hectare), minority of larges on station 5 (1,5 hectare survey; 0,5 hectare Aster). Coral with fair conditions on station 2,3,5 with percent coverage 43,59%; 26,45%; 25,2%, poor on station 4 (22,06%) and 6 (12,0%), the best category on station 1 (69,6%). Statistic model discovered for salinity ( 0/00 ) = 18,780 - 560,659 (B6 (B4+B5)).